Profil kemampuan spasial matematis siswa kelas XI SMA Negeri 1 Tuntang pada materi bangun ruang sisi lengkung - Sinta Afriyana; Helti Lygia Mampouw (STKIP PGRI Banjarmasin, 2018)
This study aims to describe the spatial ability mathematical students of class XI Senior High School of State 1 Tuntang in materials Up Space Side of the Arch. This type of research is descriptive qualitative research. Sampling in this study using purposive sampling technique. The subject of the study consisted of 3 students of class XI SMA 1 students of high ability, 1 students capable being, and 1 student of low ability. The results showed that: the subject-enabled mathematics high and the subject-enabled mathematics have spatial ability is almost the same or even the same, with only difference in his way of thinking. Way of thinking the subject of high performance more easily understood when asked to explain on the subject of the enabled being. While the subject-enabled mathematics low indeed have the spatial ability below the subject-enabled mathematics high and the subject-enabled mathematics are. The subject enabled low math when answering a question on the webs of the tube subject to low still confusion on the rotation of the mesh-netting tube is true or right. The subject enabled low math still difficult to imagine the velocity or displacement on an object, where the object is located on a different perspective.